2021
DOI: 10.7748/cnp.2021.e1794
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing nursing students’ awareness of the role of cancer research nurses to improve future recruitment

Abstract: BackgroundEarly phase oncology trials are primarily delivered by a national network of Experimental Cancer Medicine Centres, which are fundamental to taking the first step in developing new treatments for patients with cancer. In 2017, concerns about nursing recruitment and the factors affecting enrolment to research nurse posts were discussed at an Experimental Cancer Medicine Centres national nursing steering group meeting, which was attended by members from across the UK. The steering group felt there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Similar to the findings in this paper, of a lack of awareness of the role of a Clinical Research Nurse is evident in the undergraduate curriculum in the UK. Another study examined undergraduate nurses' knowledge of the role of cancer research nurses at four UK universities, and only 19% reported they had knowledge of the role, and of those, it was evident many had misconceptions (Hood et al, 2021). In addition, only a small majority would consider this a career option (10%).…”
mentioning
confidence: 99%
“…Similar to the findings in this paper, of a lack of awareness of the role of a Clinical Research Nurse is evident in the undergraduate curriculum in the UK. Another study examined undergraduate nurses' knowledge of the role of cancer research nurses at four UK universities, and only 19% reported they had knowledge of the role, and of those, it was evident many had misconceptions (Hood et al, 2021). In addition, only a small majority would consider this a career option (10%).…”
mentioning
confidence: 99%